Impact of prenatal and early life environmental exposures on normal human development. (December 2021) - Sly, Peter; Blake, Tamara; Islam, Zahir
Abstract: The global burden and pattern of disease has changed in recent decades, with fewer early childhood deaths and longer lives complicated by chronic disease. Disruption of normal human growth and development by adverse environmental exposures, especially during foetal development and early postnatal life increase life-long risk of chronic disease. The developmental timing and method of adverse exposure determines the likely impact on health and development. While many organ systems are structurally and functionally mature at birth, the CNS, respiratory and immune systems are not and undergo prolonged periods of postnatal growth and development. As such, these organ systems are vulnerable to adverse effects of both prenatal and postnatal environmental exposures. While the precise mechanisms underlying chronic disease are unknown, epigenetic mechanisms and the induction of oxidative stress are likely to be involved. An understanding of these processes is necessary to develop mitigation strategies aimed at reducing chronic disease prevalence.